Comparison of Luminex xTAG® RVP fast assay and real time RT‐PCR for the detection of respiratory viruses in adults with community‐acquired pneumonia. Issue 7 (2nd February 2016) - Luchsinger, Vivian; Prades, Yara; Ruiz, Mauricio; Pizarro, Rolando; Rossi, Patricio; Lizama, Luis; Garmendia, María Luisa; Meza, Angela; Larrañaga, Carmen; Avendaño, Luis F.
Abstract : Community‐acquired pneumonia (CAP) is the third cause of death worldwide. Viruses are frequently detected in adult CAP. Highly sensitive diagnostic techniques should be used due to poor viral shedding. Different sampling methods can affect viral detection, being necessary to establish the optimal type of sample for identifying respiratory viruses in adults. The detection rates of respiratory viruses by Luminex xTAG® RVP fast assay, real time RT‐PCR (rtRT‐PCR) (Sacace®), and immunofluorescence assay (IFA) in adult CAP were performed in nasopharyngeal swabs (NPS) and aspirates (NPA) from 179 hospitalized adults. Positivity was 47.5% for Luminex®, 42.5% for rtRT‐PCR ( P  = 0.3), and 2.7% for IFA (2.7%) ( P  < 0.0). The sensitivity, specificity, and kappa coefficient of xTAG® RVP compared with rtRT‐PCR were 84.2%, 79.6%, and 0.62%, respectively. Luminex® and rtRT‐PCR detected 65 (58.0%) and 57 (50.9%) viruses in 112 NPA and 35 (34.3%) and 31 (30.4%) in 102 NPS, respectively ( P  < 0.01). xTAG® RVP is appropriate for detecting respiratory viruses in CAP adults. Both molecular techniques yielded better results with nasopharyngeal aspirate than swabs. J. Med. Virol. 88:1173–1179, 2016 . © 2016 Wiley Periodicals, Inc.